Method for problem solution of product structure optimum automated formation - Кочергина, Светлана Станиславовна; Шевченко, Игорь Васильевич (Eastern-European Journal of Enterprise Technologies, 2014)
In this paper the improved method of product optimal composition at an engineering plant has been suggested according to the complex approach. The method uses a multi-component model of the specification tree and model of product optimal composition selection taking into account the ranking of selection criteria. By means of the Pareto plurality formation, the ranking selection criteria, the use of method of paired comparisons and adaptive integral optimality criterion it has been determined the possibility for flexible response to the changes in market conjuncture and the prospects for the production situation which makes it possible to coordinate the priorities assessments between the customer and the manufacturer. Thus, based on the existing nomenclature in the enterprise, the above-stated method allows to offer the most effective solution for the designer which forms the draft proposal to the potential customer taking into consideration particular individual requirements.